IN SILICO ADME AND TOXICITY STUDY OF SOME SELECTED ANTINEOPLASTIC DRUGS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Cancer is a serious health problem that recognized as a group of diseases involving uncontrolled cell growth. Majority of cancer chemotherapeutic agents have serious toxicity profile. Due to this use of these agents are limited. Therefore, it is essential requirement for developing new chemotherapeutic agents to devoid toxicity. In this research work, we study the pharmacokinetic, toxicity and bioactivity profile of few selected chemotherapeutic agents by In silico method. These research investigations provide the lead for the development of new cancer chemotherapeutic agents with lesser toxicity and more effectiveness.